2020
DOI: 10.46867/ijcp.2020.33.00.06
|View full text |Cite
|
Sign up to set email alerts
|

The View of Russian Psychology Students on Whether Psychology is a Science

Abstract: The Psychology as Science Scale (Friedrich, 1996) was administered to 525 psychology students from nine Russian universities to assess their beliefs about the nature of the discipline. About half of students (49.6%) generally agreed that psychology may be called a scientific discipline. Specifically, 71. 5% of the students agreed that psychology is a natural science, similar to biology, chemistry, and physics, 39. 9% of students agreed that psychological research is important and training in psychological meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 106 publications
(186 reference statements)
0
2
0
Order By: Relevance
“…Reaching a higher academic year could indicate a greater interest in the discipline, and with it, a greater desire to further delve into psychology ( Furnham & Hughes, 2014 ). However, although there is a decrease in the belief in myths according to academic year, these preconceptions do not always disappear completely ( Aleksandrova-Howell et al, 2020 ; Brown, 1983 ; Gaze, 2014 ). For example, Gardner & Dalsing (1986) found that a change only occurs when the person has participated in psychology-related courses to the subject of between 19 and 70 h. In other cases, such as that of Vaughan’s study ( 1977 ), it was found that university students from different degrees started, on average, defending 40% of a series of misconceptions about Psychology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaching a higher academic year could indicate a greater interest in the discipline, and with it, a greater desire to further delve into psychology ( Furnham & Hughes, 2014 ). However, although there is a decrease in the belief in myths according to academic year, these preconceptions do not always disappear completely ( Aleksandrova-Howell et al, 2020 ; Brown, 1983 ; Gaze, 2014 ). For example, Gardner & Dalsing (1986) found that a change only occurs when the person has participated in psychology-related courses to the subject of between 19 and 70 h. In other cases, such as that of Vaughan’s study ( 1977 ), it was found that university students from different degrees started, on average, defending 40% of a series of misconceptions about Psychology.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extensive research on myths in Psychology in other countries—see, for example, Russia ( Aleksandrova-Howell et al, 2020 ), North America ( Basterfield et al, 2020 ; Bensley & Lilienfeld, 2017 ; Brown, 1983 ; Gardner & Brown, 2013 ), United Kingdom ( Furnham, Callahan & Rawles, 2003 ; Furnham & Hughes, 2014 ; Furnham & Grover, 2019 ), or India ( Kishore et al, 2011 )—a study of the same characteristics has not yet been carried out in Spain.…”
Section: Introductionmentioning
confidence: 99%